Long‐Run Labor Market Effects of Japanese American Internment during World War II on Working‐Age Male Internees - Chin, Aimee (Journal of Labor Economics, 2005)
In 1942, all Japanese were evacuated from the West Coast and incarcerated in internment camps. To investigate the long‐run economic consequences of this historic episode, I exploit the fact that Hawaiian Japanese were not subject to mass internment. I find that the labor market withdrawal induced by the internment reduced the annual earnings of males by as much as 9%–13% 25 years afterward. This is consistent with the predictions of an economic model that equates the labor market withdrawal induced by the internment with a loss of civilian labor market experience or a loss of advantageous job matches.